Peramalan Kasus Covid-19 di DKI Jakarta dengan Model Arima - Nurul Qomariasih (CV. Syntax Corporation Indonesia, 2021)
February 2020 was the first time that Indonesian citizens were diagnosed with Covid-19. Until now, the disease caused by the Corona Virus has not subsided, it has even been declared a Global Pandemic. The purpose of this study was to find a Time Series prediction model for the number of positive cases of Covid-19 in one of the cities with the largest number of infections in Indonesia, namely Jakarta. This study uses data from Open Data Jakarta with a time span of 1 September 2020 to 30 November 2020. The model used is the Auto Regressive Integrated Moving Average (ARIMA). The resulting ARIMA parameters are (0,1,1), (1,1,0), and (1,1,1), but the best model is ARIMA (1,1,1) where all parameters are significant with p- value<α. The data used for training is 70% and 30% is used for testing. The resulting forecast value is very similar to the actual value. Thus, the model made is quite good in predicting positive cases of COVID-19 in Jakarta in the next month